Practicality and Effectiveness of Chemical Ludo Game as Learning Media for Acid and Base Materials on Learning Outcomes of Students of Class XI SMA Nurfalah - Suriani Nur; Muhammad Ikhlas Al Kutsi (Science Journal Get Press, 2025)
This study aims to evaluate the usefulness and efficiency of the Ludo Kimia game as a teaching aid on acid and base materials in relation to the learning outcomes of SMA Nurfalah class XI students. This study used a Pretest-Posttest Control Group Design, with XI MIPA 1 class as the control group and XI MIPA 2 as the experimental group at Nurfalah School. Data collection used a practicality questionnaire and pretest-posttest assessment. Practicality was analyzed using the percentage score, while effectiveness was assessed using the N-Gain method. The results showed that teachers rated the Ludo Kimia game as very practical, while students rated it as quite practical. In terms of effectiveness, this game is considered quite effective in improving student learninfgg outcomes. The experimental class showed a greater increase in conceptual understanding than the control class, with an average posttest score of 77.14 and 70.15 respectively. The N-Gain value for the experimental class was 0.59 (medium category), while the control class obtained a value of 0.51 (low category). Furthermore, the hypothesis test showed a significant difference between the two groups, with t_hitung (3.62) > t_table (1.67) at the 0.05 significance level. In conclusion, the Ludo Kimia game is a very practical media for teachers, quite practical for students, and quite effective in improving student learning outcomes on the topic of acid-base. This game can be an alternative media in learning chemistry to increase engagement and academic achievement.